Advances in the characterization and monitoring of natural organic matter using spectroscopic approaches. (15th February 2021) - Chen, Wei; Yu, Han-Qing
Highlights: Molecular spectroscopy is a key platform to characterize and monitor NOM. Advances/innovations on spectroscopic studies of NOM are summarized. Limitations of spectroscopic approaches for NOM interpretation are criticized. Perspectives on spectroscopic developments in NOM-related topics are envisaged. Abstract: Natural organic matter (NOM) is ubiquitous in environment and plays a fundamental role in the geochemical cycling of elements. It is involved in a wide range of environmental processes and can significantly affect the environmental fates of exogenous contaminants. Understanding the properties and environmental behaviors of NOM is critical to advance water treatment technologies and environmental remediation strategies. NOM is composed of characteristic light-absorbing/emitting functional groups, which are the "identification card" of NOM and susceptive to ambient physiochemical changes. These groups and their variations can be captured through optical sensing. Therefore, spectroscopic techniques are elegant tools to track the sources, features, and environmental behaviors of NOM. In this work, the most recent advances in molecular spectroscopic techniques, including UV-Vis, fluorescence, infrared, and Raman spectroscopy, for the characterization, measurement, and monitoring of NOM are reviewed, and the state-of-the-art innovations are highlighted. Furthermore, the limitations of current spectroscopic approaches for the exploration of NOM-related environmental processesand how these weaknesses/drawbacks can be addressed are explored. Finally, suggestions and directions are proposed to advance the development of spectroscopic methods in analyzing and elucidating the properties and behaviors of NOM in natural and engineered environments. Graphical abstract: Image, graphical abstract